Reincarnation - Weyn, Suzanne (New York : Scholastic Press, 2008)
When a young couple dies in prehistoric times, their love--and link to various green stones--endures through the ages as they are reborn into new bodies and somehow find a way to connect.
Mode of access: Internet.
Keywords: Love -- Fiction; Space and time -- Fiction; Reincarnation -- Fiction; Space and time -- Juvenile fiction; Reincarnation -- Juvenile fiction; Young adult fiction